Macroeconomic Factors, Capital Structure, and Liquidity Effects on Profitability of IDX Property Companies with Firm Size as Moderator - Nur Aini, Putri; Sulistiyantoro, David (Research Horizon, 2025)
The property sector is a vital pillar of Indonesia’s economy its profitability is influenced by both macroeconomic and internal company factors. This study aims to analyze the effects of inflation, interest rates, leverage, and liquidity on the profitability of property companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, with firm size as a moderating variable. A quantitative approach was employed, using multiple linear regression analysis and Moderated Regression Analysis (MRA) on secondary data from the financial reports of 10 property firms. The results reveal that Leverage has a significant adverse effect on profitability, indicating that high debt levels reduce profits. Liquidity has a significant positive effect, highlighting the importance of short-term financial stability. Inflation and interest rates have shown no significant impact, likely due to companies’ ability to adjust their pricing and diversify their funding sources. Firm size only strengthens the relationship between liquidity and profitability but does not moderate the effects of inflation, interest rates, or leverage. The study concludes that debt management and liquidity are key drivers of profitability for property firms, while macroeconomic factors can be mitigated through adaptive strategies. Practically, companies should optimize capital structure and maintain adequate liquidity, whereas investors should prioritize microeconomic indicators in decision-making.